Phylogeography of a Typical Forest Heliothermic Lizard Reveals the Combined Influence of Rivers and Climate Dynamics on Diversification in Eastern Amazonia - Cronemberger, Áurea A.; Werneck, Fernanda P.; Ávila-Pires, Teresa C. S. (Frontiers in Ecology and Evolution, 2022)
The formation of the Amazon drainage basin has been considered an important driver of speciation of several taxa, promoting vicariant events or reinforcement of barriers that restrict gene flow between opposite river margins. Several recent studies reported a set of miscellaneous events involving climatic fluctuations, geomorphological changes, and dispersal mechanisms as propellers of diversification of Amazonian rainforest taxa. Here, we show the results of dated phylogenetic, biogeographic, and populational analyses to investigate which events could better explain the current distribution of a heliothermic, active foraging lizard in the central and eastern portions of the Amazonian rainforest (besides a disjunct distribution in part of the Atlantic Forest). We sampled Kentropyx calcarata from most of its area of occurrence in Amazonia and used mitochondrial and nuclear markers to evaluate if the genetic structure agrees with evolutionary scenarios previously proposed for Amazonia. We performed phylogenetic and populational analyses to better understand the dynamics of this species in the Amazonia rainforest over time. Phylogenetic inference recovered ten K. calcarata structured lineages in eastern Amazonia, some of them limited by the Amazon River and its southern tributaries (Tapajós, Xingu, and Tocantins), although we detected occasional haplotype sharing across some of the river banks. According to molecular dating, K. calcarata diversified since Miocene–Pliocene, and some of the lineages presented signs of demographic expansion during the Pleistocene, supposedly triggered by climatic dynamics. The putative ancestral lineage of K. calcarata was distributed on the Guiana Shield, later spreading south and southeastward by dispersion. Our results indicate that Amazonian rivers acted as barriers to the dispersal of Kentropyx calcarata, but they were not the sole drivers of diversification.